Radiologic Physics Taught Through Cases - Nye, Jonathon A. (Thieme Medical Publishers, Incorporated, 2019)
High-yield, image-rich study guide presents complex physics concepts in reader-friendly format Physics is a key component of the American Board of Radiology core and certifying exams, therefore it is an essential area of study for radiology residents and young radiologists prepping for these exams. Radiology residents gather their medical physics knowledge from many sources, often beginning with their first encounter of a radiologic image. As such, Radiologic Physics Taught Through Cases by Jonathon A. Nye and esteemed contributors incorporates an image-rich, case-based layout conducive to lea.